Fracture and mechanical behavior of vacuum-assisted microwave cured unidirectional carbon woven fabric reinforced epoxy composite. (February 2021) - Kumar, Rajeev; Pathak, Himanshu; Zafar, Sunny
Woven fabric reinforced epoxy composite shown inherent favorable characteristics for aerospace industry applications. This paper comprehensively investigated the mechanical and fracture behavior of unidirectional carbon woven fabric reinforced epoxy composite using experimental and computational techniques. The composites were fabricated with two, four, and six ply laminates with cross-ply and inclined ply (45/–45) orientations. Laminates were fabricated using Vacuum-Assisted Resin Infusion Microwave Curing technique with a high fiber volume fraction of 50% for each laminate. Experimental analyses were performed to predict the behavior of composites under tensile, shear, and impact loading environment. Further, the mean-field homogenization technique coupled with the finite element method was employed to predict orthotropic material properties, fracture energy, and fracture parameters ( K IC and G IC ) of the composite. The results showed that fracture energy obtained by the computational technique was in good agreement with experimental results. The values of G IC increased with the number of plies both for cross and inclined plies orientation composites. KIC values were higher for cross plies laminates than the inclined plies laminates.